Biomass-derived porous carbons support in phase change materials for building energy efficiency: a review. (January 2022) - Jiang, Tengyao; Zhang, Yali; Olayiwola, Saheed; Lau, ChooiKim; Fan, Maohong; Ng, Kam; Tan, Gang
Abstract: Phase change materials have been used in buildings as effective latent energy storage elements because of their remarkable capability of storing thermal energy and thus have attracted great attention to ameliorate severe environmental issues caused by greenhouse gas emissions. However, the drawbacks of phase change materials such as leakage during solid–liquid phase transition process and poor thermal conductivity restrain their further development. This review paper summarizes the recent research progress in the design and synthesis of shape-stabilized phase change materials using biomass-derived porous carbons as solid supports. These carbon supports from waste resources exhibit unique features, including renewable, cost-effective, considerable thermal transfer ability, and diverse microstructures that are inherited from biomass. The applications of shape-stabilized phase change materials with composites developed from biomass in active and passive building systems are reviewed. This review concludes that employment of shape-stabilized phase change material in buildings would contribute to a reduced indoor air temperature fluctuation, improved thermal performance, and enhanced building energy efficiency. This review also provides valuable insights and promising perspectives for potential research and development of phase change materials from renewable feedstocks focused on applications in building and construction industry. Graphical abstract: Image 1 Highlights: This review summarizes shape-stabilized phase change material (SSPCM) synthesized with biomass-derived carbons. The implementations of bio-based SSPCMs in active/passive building systems are reviewed. Outlooks and future perspectives on biomass-derived SSPCMs for buildings are presented.